(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article provides for the problem of the development of the mechanism of the regional construction complex and the development of the innovative process of the regional construction complex, which makes it possible to increase the efficiency of the economic space of the region.